Investigation of endurance of AMg6 alloy under cyclic volumetric thermal deformation - I. Yu. Lesnyak; Z. N. Sokolovsky; S. V. Gavrilenko (Омский научный вестник)
Theoretical studies of the endurance of an aviation alloy of AMg6 type during its long-term cyclic volumetric temperature deformation beyond the limits of Hooke's law have been carried out. A technique has been developed for assessing the endurance of aviation alloys in cyclic volumetric temperature deformation taking into account the presence of cavities (cracks) based on bringing the cyclic volumetric temperature deformation conditions to the conditions of standard mechanical testing of samples. According to the developed method, a preliminary assessment of the endurance of the aviation alloy of AMg6 type with a workhardened and annealed surface is carried out using the available limited base of empirical data obtained on the basis of standard mechanical tests of experimental samples. The effect of the initial length of a crack in experimental samples on the endurance of the experimental samples, at which its uncontrolled growth is possible during cyclic volumetric temperature deformation, is assessed. A comparative analysis of the calculated endurance of the experimental samples with the actual endurance of the structural material (hard worked alloy AMg6) of a real orbital object such as the «Zarya» module of the international space station shows a discrepancy of no more than 12,5 %.